Mastering Microsoft Dynamics AX 2012 R3 programming : a comprehensive guide to developing maintainable and extendable solutions with Microsoft Dynamics AX 2012 R3 /: a comprehensive guide to developing maintainable and extendable solutions with Microsoft Dynamics AX 2012 R3. (2015) - Buxton, Simon; Fergusson, Mat
No abstract available